A bacteria-based search for drugs against avian and swine flu yields a potent and resistance-resilient channel blocker - Hiya Lahiri; Eitan Israeli; Miriam Krugliak; Kingshuk Basu; Yelena Britan-Rosich; Tamar Ravins Yaish; Isaiah T. Arkin (Proceedings of the National Academy of Sciences, 2025)
Influenza represents a significant threat with seasonal epidemics that can transition to global pandemics, and cross-species infection presenting a continuous challenge. While vaccines and several antiviral drugs are available, constant genetic changes vitiate these prevention and treatment options. Consequently, we decided to search for inhibitors against one of the virus’s validated drug targets, its M2 channel that is blocked by aminoadamantanes. Regrettably, widespread mutations in M2 abolish the antiflu activity of said blockers. Therefore, we devised bacteria-based genetic assays that can screen for drugs against aminoadamantane-sensitive and resistant M2 channels and map the resistance potential of any identifiable blocker. Subsequent in cellulo testing and structure–activity relationship studies yielded a synergistic combination of two compounds, Theobromine and Arainosine, that exhibited remarkable antiviral activity by directly inhibiting the virus’s channel. The drug duo was potent against H1N1 pandemic swine flu, H5N1 pandemic avian flu, and aminoadamantane-resistant and sensitive strains alike, exhibiting activity that surpassed oseltamivir, the leading antiflu drug on the market. When this drug duo was tested in an animal model, it once more outperformed oseltamivir, considerably reducing disease symptoms and viral RNA progeny. Importantly, harnessing the bacterial genetic selection, we could demonstrate that the drug duo’s potential for eliciting drug resistance is significantly smaller and molecularly distinct from that of aminoadamantanes. In conclusion, the outcome of this study represents a new potential treatment option for influenza alongside an approach that is sufficiently general and readily applicable to other viral targets.